Experience in using Total Elbow Arthroplasty at Dr. Mohammad Hoesin General Hospital Palembang (Case Series): Case Series - Nur Rachmat Lubis; Hendy Rachmat Primana Lubis (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Total elbow arthroplasty (TEA) has proven to be a reliable joint replacement procedure that has a high degree of patient satisfaction. Despite these favorable outcomes, few patientswith disabling elbow degenerative conditions have TEA recommendedto them as an alternative procedure by rheumatologists, physiatrists,or orthopedists. The semi-constrained, hinged (linked) prosthesis is the most commonly used prosthesis.This prosthesis is stable postoperatively. Patients are encouraged to do range of motionexercises and use their elbow for activities of daily living as dictated by their pain leveland status of wound healing. Wound management is critical following TEA. A posterior triceps–sparing approach, which preserves the continuity of the triceps, whenpossible, is typically used. Postoperatively the therapist and patient need to respect the integrity of the triceps and posterior incision when performing both active and passiveelbow flexion exercises and functional activities. The surgeon may choose to limitflexion range of motion based on the intraoperative inspection of the triceps tendon. We have study on 5 cases patients with elbow arthrosis and went TEA for management of elbow pain and joint limitation of movement.